Partial characterization of venom from the Colombian spider Phoneutria boliviensis (Aranae:Ctenidae) (2023)
We report on the first studies on the characterization of venom from Phoneutria boliviensis (Aranae:Ctenidae) (F. O. Pickard-Cambridge, 1897), done with Colombian species. After the electrostimulation extraction process, the venom showed physicochemical properties corresponding to a colorless and water-soluble liquid with a density of 0.86 mg/mL and 87% aqueous content. P. boliviensis venom and RP-HPLC fractions showed hemolytic activity and hydrolyzed the synthetic substrate 4-nitro-3-octanoyloxy-benzoic acid, indicating the presence of phospholipases A2 enzymes. The electrophoretic profile showed an important protein content with molecular masses below 14 kDa, and differences between male and female protein content were also revealed. The RP-HPLC venom profile exposes differences between males and female content consistent with the electrophoretic profile. Five fractions collected from the RP-HPLC displayed significant larvicidal activity. Mass analysis indicates the presence of peptides ranging from 1047.71 to 3278.07 Da. Two peptides, Ctenitoxin-Pb48 and Ctenitoxin-Pb53, were partially identified using HPLC-nESI-MS/MS, which showed a high homology with other Ctenitoxins (family Tx3) from Phoneutria nigriventer, Phoneutria keyserlingi and Phoneutria reidyi affecting voltage-gated calcium receptors (Cav 1, 2.1, 2.2 and 2.3) and NMDA-glutamate receptors. © 2015 by the authors; licensee MDPI, Basel, Switzerland.